PENGGUNAAN EDUCANDY UNTUK PEMBELAJARAN KOSAKATA DALAM KETERAMPILAN MENULIS BAHASA JERMAN SISWA SMA KELAS XII - Albiana, Ulil; Samsul, Suwarno Imam (LATERNE, 2022)
One of the elements of learning basic vocabulary mastery in German is the achievement of four language skills. The four language skills are listening, speaking, reading, and writing. In writing skills, vocabulary is the most important element needed to complete and string words into sentences. Mastery of German is not easy because in general students feel bored and less enthusiastic about learning and memorizing a lot of vocabulary. There are several applications or platforms based on android and web as a means of learning. So Educandy is used, which is a web-based educational game application as a learning medium to support the vocabulary learning process in simple German sentence writing skills. Educandy contains 45 Hobby-related vocabularies and their translations in Indonesian. The concept of educational games to learn and play makes learning more interesting so that it can help students remember vocabulary and apply the vocabulary to German writing skills. The purpose of writing this article is to test the feasibility of using the Educandy application in vocabulary learning to support the German writing skills of class XII high school students through the verification of material experts and media experts. The method used in this scientific article is Research and Development (R&D) using the ADDIE development model until the development stage. Based on the data validation results by material experts and media experts, the final results of material validation are obtained with a percentage of 80% which means the material is suitable for use in learning media with revisions in the good category. While the percentage of the final result obtained from the validation of the Educandy media is 90.66%, which means that the Educandy media deserves to be used in the very good category.